Propionate metabolism in Desulfurella acetivorans - Pettinato, Eugenio; Steiner, Thomas M.; Cassens, Eric A.; Geisberger, Thomas; Seitz, Christian; König, Simone; Eisenreich, Wolfgang; Berg, Ivan A. (Frontiers in Microbiology, 2025)
Desulfurella acetivorans is a strictly anaerobic sulfur-reducing deltaproteobacterium that can grow heterotrophically by oxidation of acetate or autotrophically with molecular hydrogen. Here we show that D. acetivorans possesses a putative operon encoding enzymes of the methylcitrate cycle of propionate oxidation and demonstrate that this bacterium is capable of propionate growth. However, activities of the methylcitrate cycle enzymes could not be detected in extracts of propionate-grown cells, and experiments with [U-13C3]propionate and comparative proteomic analysis of acetate- and propionate-grown cells suggested that the methylcitrate cycle is not active during propionate growth. Instead, propionyl-CoA assimilation proceeds via its carboxylation to methylmalonyl-CoA, which is further converted to succinyl-CoA. The latter is directed to the tricarboxylic acid (TCA) cycle, where it is converted to oxaloacetate and condenses with acetyl-CoA (produced by decarboxylation of another oxaloacetate molecule) to form citrate, which is oxidized in the TCA cycle. These results highlight the uncertainty of genomic predictions in the analysis of microbial metabolic pathways and the need for their experimental confirmation.